DETERMINANTS OF CUSTOMER’S SPENDING WITH MOBILE PAYMENT AS INTERVENING VARIABLES: CONCEPTUAL PERSPECTIVES - Berlian Karlina; Anita Wahyu Indrasti (Jurnal Ekonomika dan Manajemen, 2020)
The objective of this research is to develop specific factors that could influence customer’s spending with mobile payment as intervening variables to the conceptual perspectives. This paper examines the potential determinants to spending with conceptual perspectives: consumer features, business features, and technology features. Mobile transaction is the intervening variables that may affect the conceptual perspectives to spending. Survey questionnaires will be distributed to about 120 mobile payment users in DKI Jakarta using convenient sampling method. Data collected will be analyzed using regression technique to determine the significant levels of interactions between the dependent, intervening variables, and independent variables. The result of this study could help firms understand the consumer’s perspective to spend by using mobile payment as media of transaction. This could also be relevant for Indonesia to face Industry Revolution 4.0. This research would also provide useful data that could help the industry determine consumers’ mobile payment needs in the context of Indonesia. The empirical insights from this study would also be useful for theory building.